2019
DOI: 10.1038/s41598-019-51719-3
|View full text |Cite
|
Sign up to set email alerts
|

Mantle degassing along strike-slip faults in the Southeastern Korean Peninsula

Abstract: On September 12, 2016, a ML 5.8 earthquake hit Gyeongju in the southeastern part of the Korean Peninsula (SeKP), although the area is known to be far from the boundary of the active plate. A number of strike-slip faults are observed in heavily populated city areas (e.g., Busan, Ulsan, Pohang, and Gyeongju). However, dissolved gases related to the active faults have rarely been studied despite many groundwater wells and hot springs in the area. Here we report new results of gas compositions and isotope values o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 52 publications
(93 reference statements)
2
21
0
Order By: Relevance
“…Based on the N 2 -Ar-He ternary diagram ( Figure 2), nonreactive gases (N 2 , Ar, and He) in the Heunghae and Yeonil areas display a two-component mixing relationship between the mantle and atmospheric end members. Lee et al [9] have shown that fault gases in the southeastern Korean peninsula are continental gases rather than subduction zone gases. Dissolved gases in groundwater from the Sinkwang area are atmospheric with low He/Ar ratios (0.003 to 0.001).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on the N 2 -Ar-He ternary diagram ( Figure 2), nonreactive gases (N 2 , Ar, and He) in the Heunghae and Yeonil areas display a two-component mixing relationship between the mantle and atmospheric end members. Lee et al [9] have shown that fault gases in the southeastern Korean peninsula are continental gases rather than subduction zone gases. Dissolved gases in groundwater from the Sinkwang area are atmospheric with low He/Ar ratios (0.003 to 0.001).…”
Section: Discussionmentioning
confidence: 99%
“…Dissolved gases in groundwater from the Sinkwang area are atmospheric with low He/Ar ratios (0.003 to 0.001). Lee et al [9] addressed that some gas samples which are severely contaminated by air in southeastern Korea are due to shallow well depths (130 to 296 m). However, in the Heunghae and Yeonil areas, it is unlikely that well depths (Table 1) and contribution from deeply derived gases are relevant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This process, also termed mantle degassing, is the transition of volatiles from the mantle (supercritical) to the subcritical zone of the upper crust fueled by lower pressure of volatiles near the surface compared to the mantle 20 . Modern Earth has few areas with active mantle degassing, which are usually restricted to terrestrial volcanoes or hydrothermal vents in oceans 21,22,23,24 . At hydrothermal vents, chemolithoautotrophs initiate the microbial trophic network and proliferate at high rates leading to high microbial cell numbers 1 .…”
Section: Introductionmentioning
confidence: 99%
“…In addition to these, several faults were newly included as active faults associated with the M 5.8 earthquake (Lee et al 2018(Lee et al , 2019. Several cultural heritage sites, including the capital of the longest dynasty in ancient Korea, as well as many industrial facilities, including nuclear power plants, are located in the vicinity of these faults.…”
Section: Introductionmentioning
confidence: 99%